2021
DOI: 10.15376/biores.16.3.5721-5732
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic and anti-inflammatory effects of hydrosol extracted from Zanthoxylum schinifolium branch

Abstract: Zanthoxylum schinifolium Sieb. et Zucc. (syn. Fagara schinifolia Engler) was studied for its potential anti-inflammatory properties. The hydrosol extract prepared from the Z. schinifolium branch was analyzed by gas chromatography/mass spectrometry. Here, five main chemical components were identified in the hydrosol of the branches of this shrub. The main chemical compounds in the branch inhibited both an Immunoglobulin E (IgE)-antigen complex and a dinitrophenyl-bovine serum albumin (DNP-BSA)-induced β-hexosam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Hydrosols have recently started to receive a lot of credit in a variety of areas, such as food (e.g., flavouring, preservatives, and sanitisers) [ 18 , 19 ], cosmetic and perfumery [ 20 ], aromatherapy [ 21 ], agriculture (e.g., biopesticides and repellents) [ 22 ], pharmaceutical (e.g., natural antibiotics, antioxidants and anti-inflammatory agents) [ 17 , 23 ], and medical (e.g., antimicrobial and antitumor agents) [ 24 ]. According to circular economy principles, using industrial by-products can be a sustainable way to address the environmental problems caused by waste discharging.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrosols have recently started to receive a lot of credit in a variety of areas, such as food (e.g., flavouring, preservatives, and sanitisers) [ 18 , 19 ], cosmetic and perfumery [ 20 ], aromatherapy [ 21 ], agriculture (e.g., biopesticides and repellents) [ 22 ], pharmaceutical (e.g., natural antibiotics, antioxidants and anti-inflammatory agents) [ 17 , 23 ], and medical (e.g., antimicrobial and antitumor agents) [ 24 ]. According to circular economy principles, using industrial by-products can be a sustainable way to address the environmental problems caused by waste discharging.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many hydrolates are widely exploited in aromatherapy, cosmetic formulations, food industry and organic agriculture [Aćimović et al 2020a]. Several studies reported their antioxidant, anti-allergic, antiinflammatory antimicrobial and fungicidal properties as well as cytotoxic or anti-enzymatic activity [Boyraz & Ozcan 2006;Ko et al 2017;Shen et al 2017;D'Amato et al 2018;Mohamed Gameil et al 2019;Ha et al 2021;Pérez-Izquierdo et al 2022;Yu et al 2022]. Allelopathic effect was also studied to find alternative agricultural strategies, for example in weed control in order to reduce the use of traditional agrochemicals along with their side effects on the environment and human health.…”
Section: Introductionmentioning
confidence: 99%